Jeju Island- A “Visa-Free” South Korean Destination, Not Free to All: A Legal Remedy - Garon, Nicolas Patrick (American Journal of Trade and Policy, 2023)
Jeju Island, a picturesque island off the southern coast of South Korea, is a popular destination known for its stunning natural landscapes and unique culture. Unlike South Korea’s general visa policy, which requires visas for many nationalities, Jeju Island offers a more lenient visa-free policy, allowing most travelers to stay for up to 30 days without a visa, providing they satisfy the requirement of arriving via direct flight outside mainland South Korea. However, the island’s visa policy is only partially inclusive, as it excludes nationals from 23 countries designated by the South Korean Ministry of Justice. While allowing visa-free travel for tourists is a concept explored previously, South Korea’s restriction on certain nationalities undercuts its goal of promoting tourism and economic development on Jeju Island. Interestingly, other countries that have visa-free island policies do not impose such restrictions, including Vietnam’s Phú Quốc Island, Iran’s Kish and Qeshm Islands, and Norway’s Svalbard. This article delves into Jeju Island’s visa policy, the list of excluded countries, and the policies of other countries with visa-free islands. It proposes a straightforward legal remedy that could promote more inclusive tourism by allowing all nationalities to visit Jeju Island without visa restrictions. Such a move would enhance the island’s reputation as a welcoming and inclusive tourist destination and foster greater international cooperation.